1996
DOI: 10.1037/0003-066x.51.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Exploring careers with a typology: What we have learned and some new directions.

Abstract: Holland’s (1985a) typology of persons and environments is outlined, and support for the theory as an explanation of stability and change in careers and work satisfaction is summarized. Studies show that people flourish in their work environment when there is a good fit between their personality type and the characteristics of the environment. Lack of congruence between personality and environment leads to dissatisfaction, unstable career paths, and lowered performance. The results of recent research designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
293
0
72

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 458 publications
(378 citation statements)
references
References 43 publications
13
293
0
72
Order By: Relevance
“…environments is contained in Holland's theory of vocational personalities and work environments (Holland, 1958(Holland, , 1996(Holland, , 1997. Six occupational environments are described in this model that pose very different requirements to individual employees (Holland, 1997).…”
Section: Occupational Environments and Trait Changementioning
confidence: 99%
“…environments is contained in Holland's theory of vocational personalities and work environments (Holland, 1958(Holland, , 1996(Holland, , 1997. Six occupational environments are described in this model that pose very different requirements to individual employees (Holland, 1997).…”
Section: Occupational Environments and Trait Changementioning
confidence: 99%
“…Assessment of these potential factor solutions indicated that the six-factor configuration was the best fit and most coherent with the theoretical model grounding the ATPH, corresponding to the career types proposed by Holland (1996Holland ( , 1997. Table 1 presents a synthesis of results found in this exploratory analysis, as well as coefficients of internal consistency (Cronbach's alpha) for each of the factors extracted.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis predicts that the prototypical distances in the multidimensional area between the adjacent types (R-I; I-A; A-S; S-E; E-C and C-R) is greater than the distance between the alternate types (e.g., R-A; I-S; A-E; S-C; E-R and C-I); which in turn is greater than the distance between the opposite types (e.g., R-S; I-E and C-A (Holland, 1996(Holland, , 1997Rounds & Tracey, 1996;Tracey, Watanabe, & Schneider, 1997). …”
mentioning
confidence: 99%
See 2 more Smart Citations